A Highly Stretchable and Self‐Healing Supramolecular Elastomer Based on Sliding Crosslinks and Hydrogen Bonds. (20th December 2019) - Du, Ruichun; Xu, Zhicheng; Zhu, Cong; Jiang, Yuanwen; Yan, Hongping; Wu, Hung‐Chin; Vardoulis, Orestis; Cai, Yifeng; Zhu, Xiangyang; Bao, Zhenan; Zhang, Qiuhong; Jia, Xudong
Abstract: The long application life and stable performance of stretchable electronics have been putting forward requirements for both higher mechanical properties and better self‐healing ability of polymeric substrates. However, for self‐healing materials, simultaneously improving stretchability and robustness is still challenging. Here, by incorporating sliding crosslinker (polyrotaxanes) and hydrogen bonds into a polymer, a highly stretchable and self‐healable elastomer with good mechanical strength is achieved. The elastomer exhibits very high stretchability, such that it can be stretched to 2800% with a fracture strength of 1.05 MPa. Moreover, the elastomer can achieve nearly complete self‐healing (93%) at 55 °C. Next, tensile tests under different temperatures, step extension experiments, and in situ small angle X‐ray scattering confirm that the excellent stretchability is attributed to the combined effects of sliding cyclodextrins along guest chains and hydrogen bonds. Furthermore, a strain sensor by coating the single‐wall carbon nanotubes onto the surface of the elastic substrate is fabricated. Abstract : A new strategy, by incorporating sliding crosslinks and hydrogen bonds into a polymer to achieve a highly stretchable and self‐healable elastomer with good mechanical strength, is reported in this work.